2022
DOI: 10.1186/s41120-022-00055-4
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of poloxamer 188 in buffered formulation conditions

Abstract: Poloxamer 188 (P188) as a non-ionic surfactant is used in proteinaceous formulations to prevent protein adsorption to hydrophobic surfaces and unfolding at interfaces, preventing the formation of aggregates and particles. Its chemical intactness is crucial to the stability of drug products due to its protecting effects at interfaces. In order to identify and mitigate potential risks that might cause the degradation of P188 during the manufacturing process and storage, in the current work, the stability of P188… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For a more detailed description see Bollenbach et al (2022) . Nevertheless, poloxamers 188 are also able to be oxidized, which results in oxidized POE and PPO species such as formaldehyde, propionaldehyde, and acetaldehyde depending on the buffer system and the applied stress (solution stability of poloxamer) ( Bollenbach et al, 2022 ; Wang et al, 2019 ; Kim et al, 2014 ), which is a problem in histidine buffer as well as in presence of trace metals ( Wang et al, 2019 ; Chen et al, 2022 ). Another alternative is cyclodextrin as it is already used in some formulations, with hydroxypropyl-ß-cyclodextrin (HPßCD) being the most extensively studied ( Jenke, 2006 ; Zhou et al, 2010b ; Rowe et al, 2009 ; Wu et al, 2021 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…For a more detailed description see Bollenbach et al (2022) . Nevertheless, poloxamers 188 are also able to be oxidized, which results in oxidized POE and PPO species such as formaldehyde, propionaldehyde, and acetaldehyde depending on the buffer system and the applied stress (solution stability of poloxamer) ( Bollenbach et al, 2022 ; Wang et al, 2019 ; Kim et al, 2014 ), which is a problem in histidine buffer as well as in presence of trace metals ( Wang et al, 2019 ; Chen et al, 2022 ). Another alternative is cyclodextrin as it is already used in some formulations, with hydroxypropyl-ß-cyclodextrin (HPßCD) being the most extensively studied ( Jenke, 2006 ; Zhou et al, 2010b ; Rowe et al, 2009 ; Wu et al, 2021 ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…P188, identified to be nontoxic and nonirritating, is suitable for parenteral administration . Its degradation occurred only at high temperatures (e.g., ≥40 °C) or under specific conditions, for example, the presence of histidine, radicals, or trace metals. , However, it has not found widespread use in protein formulations. Among 131 approved antibody products for human use, only 4 contained P188 .…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, polysorbate-80 does not form protein–surfactant complexes; this non-ionic surfactant inhibits protein adsorption by their preferential location at an interface to which they show sufficient affinity. Also, at low concentrations, it has been reported that poloxamer 188 at 40 °C was stable for up to 6 months in certain buffer conditions [ 30 , 31 ]. The different mechanisms of action of the two non-ionic surfactants evaluated and their stability at high temperatures might have influenced the preservation of the virus differently.…”
Section: Discussionmentioning
confidence: 99%